Influencia de la gestión de servicios básicos en el desarrollo social de la parroquia Guanazán del cantón Zaruma. año 2021 - Sigcho Pérez, Beverly Noelly; Zari Cuenca, Katherine Viviana (Machala : Universidad Técnica de Machala, 2022)
Quality basic services contribute to meeting vital needs, achieving improvement in the living conditions of citizens, enabling good community living and social development. However, important changes have been achieved in society regarding sustainability and sustainability, at present they are still present in neighborhoods, parishes and vulnerable communities of Ecuador, which lack basic services, violating the universal and constitutional rights that the inhabitants have. The research on the management of basic services and social development in the Guanazán parish analyzes the influence that the management of parish and municipal authorities has on the coverage of these services. The context is reflected in knowing the direct reality and proposing changes that favor improving their optimal living conditions of the population. The place of study is located in the Province of El Oro, Zaruma Canton, Guanazán Parish, its limits, north, With the Abañín Parish, south With the Salvias Parish, east With the Province of Loja and west With the Chilla Canton. The central question that guides the systematization of the problem is, What importance in the social development of the Guanazán parish has the management of basic services carried out by the local GAD, the general objective of the project has been to determine the importance of the management of basic services carried out by the local GAD in the social development of the parish Guanazán. And as specific objectives, the identification of the characteristics adopted by the provision of basic services; specification of the characteristics assumed by the management of the parish GAD in relation to the provision of basic services, identification of the role played by the community in decision-making for the provision of basic services oriented to social development and consequences in the social-community development generated by the inadequate management for the provision of basic services in the parish. The methodology for the research is quantitative, sociologically based on the structural functionalism of Talcott Parsons whose epistemological approach is the hypothetical deductive, applying techniques such as, the survey by means of a form and the descriptive observation that facilitated the identification of the problems of the context. Through the results obtained, it is reflected that the management by the parish and municipal authorities is not efficient, added to the low participation of the communities in decision-making about the provision of basic services, generating a low index in the social development of the parish. Based on the results, an intervention proposal is proposed, with the theme. Training plan to strengthen the participation of neighborhood managers and leaders oriented to the management of basic service works in the Guanazán parish consequently, the elaboration of three training workshops is given, alignment and training in transformational leadership, management and planning for community development and community participation-local progress, so that the participation of neighborhood managers and leaders in the management of basic service works in the parish is encouraged and contribute to the cooperation of the inhabitants in order to solve a part of the problem.
Los servicios básicos de calidad contribuyen a cubrir las necesidades vitales, logrando el mejoramiento en las condiciones de vida de los ciudadanos, posibilitando el buen vivir comunitario y desarrollo social. No obstante, se han logrado importantes cambios en la sociedad referente a la sostenibilidad y sustentabilidad, en la actualidad aún se encuentran presentes en barrios, parroquias y comunidades vulnerables del Ecuador, que carecen de servicios básicos, vulnerando los derechos universales y constitucionales que tienen los habitantes. La investigación sobre la gestión de servicios básicos y el desarrollo social en la parroquia Guanazán, analiza la influencia que tiene la gestión de las autoridades parroquiales y municipales para la cobertura de estos servicios. El contexto se refleja en conocer la realidad directa y proponer cambios que favorezcan a mejorar sus óptimas condiciones de vida de la población. El lugar de estudio se encuentra ubicado en la Provincia de El Oro, cantón Zaruma, Parroquia Guanazán, sus límites, norte con la Parroquia Abañín, sur con la Parroquia Salvias, este con la Provincia de Loja y oeste con el Cantón Chilla. La pregunta central que orienta a la sistematización del problema es, Qué trascendencia en el desarrollo social de la parroquia Guanazán tiene la gestión de los servicios básicos realizada por el GAD local. Se ha planteado el objetivo general del proyecto es determinar la trascendencia que tiene la gestión de los servicios básicos realizada por el GAD local en el desarrollo social de la Parroquia Guanazán. Y como objetivos específicos, la identificación de las características que adoptan la dotación de servicios básicos, especificación de las características que asume la gestión del GAD parroquial en relación a la dotación de servicios básicos, identificación del rol que desempeña la comunidad en la toma de decisiones para la dotación de servicios básicos orientados al desarrollo social y las consecuencias en el desarrollo social-comunitario que genera la inadecuada gestión para la dotación de servicios básicos en la parroquia. La metodología para la investigación es cuantitativa, fundamentada sociológicamente en el estructural funcionalismo de Talcott Parsons cuyo enfoque epistemológico es el hipotético deductivo, aplicando técnicas como: la encuesta por medio de un formulario y la observación descriptiva que facilitaron la identificación de las problemáticas del contexto. Mediante los resultados obtenidos se refleja que la gestión por parte de las autoridades parroquiales y municipales no es eficiente, sumado a la escasa participación de las comunidades en la toma de decisiones acerca de la dotación de servicios básicos, generando un bajo índice en el desarrollo social de la parroquia. En base a los resultados se plantea una propuesta de intervención, con el tema. Plan de capacitaciones para fortalecer la participación de los directivos y dirigentes barriales orientado a la gestión de obras de servicios básicos en la parroquia Guanazán en consecuencia, se da la elaboración de tres talleres de capacitación, alineación y formación en liderazgo transformacional, gestión y planificación para el desarrollo comunitario y participación comunitaria-progreso local, de modo que, se fomente la participación de los directivos y dirigentes barriales en la gestión de obras de servicios básicos en la parroquia y contribuir a la cooperación de los habitantes con el fin de dar solución a una parte del problema.
Keywords: GESTION MUNICIPAL; SERVICIO BASICO; DESARROLLO SOCIAL